COUNTER-TERRORISM IN INDONESIA - Meliala, Jordan Sebastian (Brawijaya Law Journal, 2015)
Since the incident of World Trade Center (WTC) in USA, Indonesia has become an easy target for the next terrorism. Counterterrorist campaigns can be undertaken by military and paramilitary forces. Counterterrorism refers to proactive policies that specifically seek to eliminate terrorist environments and groups, Regardless of which policy is selected, the ultimate goal of counterterrorism is clear: to save lives by proactively preventing or decreasing the number of terrorist attacks. But, so far the Government of Indonesia is only able to capture the terrorists but is unable to eradicate terrorism. Therefore, the government of Indonesia still needs a comprehensive ways to counter terrorism in Indonesia